Understanding Culture Clashes and Catalyzing Change: A Culture Cycle Approach - Hamedani, Mar Yam G.; Markus, Hazel Rose (Frontiers in Psychology, 2019)
U.S. Americans repeatedly invoke the role of “culture” today as they struggle to make sense of their increasingly diverse and divided worlds. Given the demographic changes, cultural interactions and hybridizations, and shifting power dynamics that many U.S. Americans confront every day, we ask how psychological scientists can leverage insights from cultural psychology to shed light on these issues. We propose that the culture cycle—a tool that represents culture as a multilayered, interacting, dynamic system of ideas, institutions, interactions, and individuals—can be useful to researchers and practitioners by: (1) revealing and explaining the psychological dynamics that underlie today’s significant culture clashes and (2) identifying ways to change or improve cultural practices and institutions to foster a more inclusive, equal, and effective multicultural society.